Advertising as a search deterrent. (13th November 2017) - Wang, Chengsi
Abstract: This article examines a monopoly firm's incentive to disclose information through advertising when consumers can choose between buying immediately and searching for additional information. Because sales drop when search reveals low match values to consumers, the firm has an incentive to deter search. We show that partial information disclosure emerges as a useful tool for search deterrence when search costs are low. Informative advertising and consumer search can be viewed as complements in producing information. Although transparency policies reduce search expenditures and improve purchase decisions, whether they are socially desirable depends on the magnitude of search costs.